3α-androstanediol, but not testosterone, attenuates age-related decrements in cognitive, anxiety, and depressive behavior of male rats - Frye, Cheryl A.; Edinger, Kassandra L.; Lephart, Edwin D.; Walf, Alicia A. (Frontiers in Aging Neuroscience, 2010)
Some hippocampally-influenced affective and/or cognitive processes decline with aging. The role of androgens in this process is of interest. Testosterone (T) is aromatized to estrogen, and reduced to dihydrotestosterone (DHT), which is converted to 5α-androstane, 3α, 17α-diol (3α-diol). To determine the extent to which some age-related decline in hippocampally-influenced behaviors may be due to androgens, we examined the effects of variation in androgen levels due to age, gonadectomy, and androgen replacement on cognitive (inhibitory avoidance, Morris water maze) and affective (defensive freezing, forced swim) behavior among young (4-months), middle-aged (13-months), and aged (24-months) male rats. Plasma and hippocampal levels of androgens were determined. In experiment 1, comparisons were made between 4-, 13-, and 24-month old rats that were intact or gonadectomized (GDX) and administered a T-filled or empty silastic capsule. There was age-related decline in performance of the inhibitory avoidance, water maze, defensive freezing, and forced swim tasks, and hippocampal 3α-diol levels. Chronic, long-term (1-4 weeks) T-replacement reversed the effects of GDX in 4- and 13-month old, but not 24-month old, rats in the inhibitory avoidance task. Experiments 2 and 3 assessed whether acute subcutaneous T or 3α-diol, respectively, could reverse age-associated decline in performance. 3α-diol, but not T, compared to vehicle, improved performance in the inhibitory avoidance, water maze, forced swim, and defensive freezing tasks, irrespective of age. Thus, age is associated with a decrease in 3α-diol production and 3α-diol administration reinstates cognitive and affective performance of aged male rats.